(untitled) (Indian Journal of Experimental Biology (IJEB), 2023)
The World Health Organization (WHO) has defined Vancomycin intermediate Staphylococcus aureus (VISA) and Vancomycin resistant Staphylococcus aureus (VRSA) as high priority pathogens. VISA and VRSA are produced by different mechanisms, hence VISA cannot convert to VRSA. Consequently, upon vancomycin treatment of VSSA isolates, there can be emergence of VISA but not its conversion to VRSA. But we observed that when VSSA (MIC ≤2 µg/mL) isolates, lacking vanA or vanB genes, are grown under vancomycin stress for 60 days, 4 out of 8 isolates get converted to VISA (MIC = 4-8 µg/mL), and 1 converted to VRSA (MIC ≥16 µg/mL). Further, the VRSA isolate had a vancomycin MIC that was 8-fold higher than that of its sensitive counterpart. Hence, the VRSA has been interpreted as a heteroresistant isolate. To dissect the molecular underpinning of this transient resistance pattern, we analyzed the gene expression profile of these isolates and publicly available datasets. pbp2 gene was observed to be consistently upregulated in all the VISA isolates except the heteroresistant isolate. Pathway analysis revealed upregulation of peptidoglycan biosynthesis in VISA isolates. However, the distinct transcriptional profile of the heteroresistant isolate (with upregulation of recR, ureC and atl) suggests potential role of increased mutation due to SOS response or biofilm formation in this phenotype.